2002
DOI: 10.1001/archinte.162.15.1729
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Molecular-Weight Heparin and Warfarin for the Secondary Prevention of Venous Thromboembolism in Patients With Cancer

Abstract: These results confirm that warfarin is associated with a high bleeding rate in patients with venous thromboembolism and cancer. Prolonged treatment with low-molecular-weight heparin may be as effective as oral anticoagulants and may be safer in these cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
195
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 748 publications
(210 citation statements)
references
References 19 publications
2
195
2
2
Order By: Relevance
“…[1][2][3] According to the results of several randomized clinical trials, [4][5][6][7] international guidelines recommend the use of sub-therapeutic doses of low-molecular-weight heparins (LMWH) for the long-term prevention of recurrent VTE in all cancer patients. [8][9][10] However, in clinical practice many clinicians still administer VKA to their cancer patients, especially to those with limited disease and longer life expectancy.…”
Section: Recurrent Thromboembolism and Major Bleeding During Oral Antmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] According to the results of several randomized clinical trials, [4][5][6][7] international guidelines recommend the use of sub-therapeutic doses of low-molecular-weight heparins (LMWH) for the long-term prevention of recurrent VTE in all cancer patients. [8][9][10] However, in clinical practice many clinicians still administer VKA to their cancer patients, especially to those with limited disease and longer life expectancy.…”
Section: Recurrent Thromboembolism and Major Bleeding During Oral Antmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, assessment of CMV-specific T-cell immunity has not had a major impact on the clinical management of CMV infection in these patients, as no widely accepted thresholds in the number of CMV-specific T cells providing protection have been established. In the present study, we optimized a simple intracellular cytokine staining (ICS), and investigated whether enumeration of CMV-specific interferon (IFN)γ CD8 + and CD4 + T cells early after transplantation could reliably predict the development of active CMV infection within 100 days after transplantation.…”
Section: Cells Early After Allogeneic Stem Cell Transplantation May Imentioning
confidence: 99%
“…In these studies, LMWH was compared to vitamin K antagonists (VKA) for the treatment of acute VTE in cancer patients. The pivotal CLOT study showed a significant reduction in VTE recurrence,4 while three other smaller studies showed no difference in efficacy or safety outcomes,30, 31, 32 and the most recent CATCH study33 showed a nonsignificant reduction in VTE recurrence, but a significantly decreased risk of clinically relevant non‐major bleeding (CRNMB) in the LMWH arm. We performed a meta‐analysis of the summary data from these studies using Review Manager (RevMan) [Computer program].…”
Section: Treatment Of Cancer‐associated Thrombosismentioning
confidence: 99%
“…The use of low molecular weight heparin for secondary prevention of venous thromboembolism in cancer patients may reduce the complication rate [9].…”
Section: Comparison Of Lowmolecular Weight Heparin and Warfarinmentioning
confidence: 99%